A Submicrosecond-Response Ultrafast Microwave Ranging Method Based on Optically Generated Frequency-Modulated Pulses - Yifei Sun; Yongchao Chen; Longhuang Tang; Xing Jia; Heli Ma; Xiang Wang; Long Chen; Shenggang Liu; Tianjiong Tao; Jian Wu; Chengjun Li; Shuanyu Liu; et al. (Sensors)
An ultrafast microwave ranging method based on optically generated frequency-modulated microwave pulses is proposed in this study. The theoretical analysis demonstrated that nanosecond-scale linear frequency modulation microwave pulse can be obtained by femtosecond laser interference under the condition of unbalanced dispersion, which can be used to achieve a high temporal resolution of the displacement change in the measurement by the principle of frequency modulation continuous wave (FMCW) radar. The proof-of-principle experiment successfully measured the displacement change with an error of 2.5 mm and a range of 0.6 m, with a response time of 468 ns. Compared to existing microwave ranging technologies, the temporal resolution was improved by two orders of magnitude, which greatly improves the temporal resolution of distance measurement in the field of microwave FMCW radar.